The Kyoto Protocol of 1997 Flexibility Mechanisms - M. N. Kopylov; E. A. Yakusheva (Московский журнал международного права)
The article discusses the flexibility mechanisms contained in the Kyoto Climate Protocol of 1997, among which the document classifies clean development mechanism, joint implementation and emission trading. Special attention is paid to the already existing experience in the field of foundation and functioning of carbon markets and exchanges.